AN ANALYSIS OF ENGLISH PREPOSITIONAL ERRORS IN SENIOR HIGH SCHOOL’S STUDENTS IN INDONESIA - Nurfithri Fithri (Ma'soem University, 2021)
This research is aimed at identifying the grammatical errors focused on English Prepositions produced by Senior High School’s Students in Garut. The objectives of this research are to investigate the types of grammatical errors focused on English prepositions by Senior High School Students and to find the most frequent type of these errors. The method of this research is the descriptive qualitative method. The researcher gave the test consists of 20 sentences that were incomplete in narrative composition. The students were asked to complete the sentence with the correct preposition chosen in multiple-choice. The finding shows that the twelfth-grade students as the participant contributed three types of errors on the use of prepositions to complete the sentences. Those errors are 30,93% in the error of omission, 26,25% in the error of insertion, and 42,81% in the error of selection. Thus, the most frequent type of errors produced by students of twelfth grade is the error of selection that reaches 42,81%. It indicates that students faced difficulties in using prepositions appropriately.